Developing vitamin D dietary guidelines and the lack of 25-hydroxyvitamin D assay standardization: The ever-present past. Issue 164 (November 2016) - Sempos, C.T.; Durazo-Arvizu, R.A.; Binkley, N.; Jones, J.; Merkel, J.M.; Carter, G.D.
Highlights: 25(OH)D used to define states of vitamin D status, e.g., deficient, and sufficient. Unstandardized 25(OH)D data is the fundamental limitation thwarting that effort. Vitamin D Standardization Program (VDSP) was developed to correct this problem. In all future research, collect only 25(OH)D data standardized using VDSP methods. VDSP has developed methodology for standardizing stored serum samples too. Standardization of past research key to defining vitamin D status states is essential. Abstract: Unstandardized laboratory measurement of 25-hydroxyvitamin D (25(OH)D) confounds efforts to develop clinical and public health vitamin D guidelines. The Vitamin D Standardization Program (VDSP), an international collaborative effort, was founded in 2010 to correct this problem. Nearly all published vitamin D research is based on unstandardized laboratory 25(OH)D measurements. While it is impossible to standardize all old data, it may be possible to identify a small subset of prior studies critical to guidelines development. Once identified it may be possible to calibrate their 25(OH)D values to the NIST and Ghent University reference measurement procedures using VDSP methods thereby permitting future guidelines to be based on standardized results. We simulated the calibration of a small set of ten clinical trials of vitamin D supplementation on achieved 25(OH)D under minimal sun exposure. These studies were selected because they played a prominent role in setting the 2010 vitamin D dietary reference intakes (DRI). Using random-effects meta-regression analysis, Vitamin D External Quality Assessment (DEQAS) data on assay bias was used to simulate the potential bias due to the lack of assay standardization by calibrating the achieved 25(OH)D levels from those 10 studies to: (1) the largest negative, and (2) the largest positive bias from the DEQAS all laboratory trimmed mean (ALTM) for the appropriate assay and year of analysis. For a usual vitamin D intake of 600 IU/day the difference in mean achieved 25(OH)D values for those two options was 20 nmol/L. However, without re-calibration of 25(OH)D values it is impossible to know the degree to which any of the current guidelines may have been biased. This approach may help stimulate the search for and standardization of that small subset of key studies and, in the cases where standardization is impossible, to identify areas of urgently needed vitamin D research.